Quinupristin/dalfopristin attenuates the inflammatory response and reduces the concentration of neuron-specific enolase in the cerebrospinal fluid of rabbits with experimental Streptococcus pneumoniae meningitis - Trostdorf, Frank; Reinert, R. R.; Schmidt, H.; Nichterlein, Thomas; Stuertz, K.; Schmitz-Salue, M.; Sadowski, I.; Brück, W.; Nau, R. (The journal of antimicrobial chemotherapy, 1999)
The inflammatory response following initiation of antibiotic therapy and parameters of neuronal - damage were compared during intravenous treatment with quinupristin/dalfopristin (100 mg/kg - as either a short or a continuous infusion) and ceftriaxone (10 mg/kg/h) in a rabbit model of Streptococcus pneumoniae meningitis. With both modes of administration, - quinupristin/dalfopristin was less bactericidal than ceftriaxone. However, the concentration of - proinflammatory cell wall components (lipoteichoic acid (LTA) and teichoic acid (TA)) and the - activity of tumour necrosis factor (TNF) in cerebrospinal fluid (CSF) were significantly lower in - the two quinupristin/dalfopristin groups than in ceftriaxone-treated rabbits. The median LTA/TA - concentrations (25th/75th percentiles) were as follows: (i) 14 h after infection: 133 (72/155) - ng/mL for continuous infusion of quinupristin/dalfopristin and 193 (91/308) ng/mL for short - duration infusion, compared with 455 (274/2042) ng/mL for ceftriaxone (P = - 0.002 and 0.02 respectively); (ii) 17 h after infection: 116 (60/368) ng/mL for continuous - infusion of quinupristin/dalfopristin and 117 (41/247) ng/mL for short duration infusion, - compared with 694 (156/2173) ng/mL for ceftriaxone (P = 0.04 and 0.03 - respectively). Fourteen hours after infection the median TNF activity (25th/75th percentiles) was - 0.2 (0.1/1.9) U/mL for continuous infusion of quinupristin/dalfopristin and 0.1 (0.01/3.5) U/mL - for short duration infusion, compared with 30 (4.6/180) U/mL for ceftriaxone (P = - 0.02 for each comparison); 17 h after infection the TNF activity was 2.8 (0.2/11) U/mL - (continuous infusion of quinupristin/ dalfopristin) and 0.1 (0.04/6.1) U/mL (short duration - infusion), compared with 48.6 (18/169) U/mL for ceftriaxone (P = 0.002 and - 0.001). The concentration of neuron-specific enolase (NSE) 24 h after infection was significantly - lower in animals treated with quinupristin/ dalfopristin: 4.6 (3.3/5.7) µg/L (continuous - infusion) and 3.6 (2.9/4.7) µg/L (short duration infusion) than in those treated with - ceftriaxone (17.7 (8.8/78.2) µg/L) (P = 0.03 and 0.009 respectively). In - conclusion, antibiotic treatment with quinupristin/dalfopristin attenuated the inflammatory - response within the subarachnoid space after initiation of antibiotic therapy. The concentration of - NSE in the CSF, taken as a measure of neuronal damage, was lower in - quinupristin/dalfopristin-treated rabbits than in ceftriaxone-treated rabbits.
Gesehen am 30.05.2022